piRNAs initiate an epigenetic memory of non-self RNA in the C. elegans germline - Shirayama, Masaki (2012)
Organisms exhibit a fascinating array of gene-silencing pathways, which have evolved in part, to confront invasive nucleic acids such as transposons and viruses. A key question raised by the existence of these pathways is how do they distinguish “self” from “non-self” nucleic acids? Evidence exists for a number of mechanisms that might facilitate detection of foreign sequences including mechanisms that sense copy-number, unpaired DNA, or aberrant RNA (e.g. dsRNA). Here we describe an RNA-induced epigenetic silencing pathway, RNAe, that permanently silences single-copy transgenes. We show that the Piwi Argonaute PRG-1 and its genomically encoded piRNA cofactors initiate RNAe, while maintenance depends on chromatin factors and the WAGO Argonaute pathway. Our findings support a model in which PRG-1 scans for foreign sequences, while two other Argonaute pathways serve as epigenetic memories of “self” and “non-self” RNAs. These findings suggest how organisms may utilize RNAi-related mechanisms not only to recognize and silence foreign genes, but also to keep inventory of all genes expressed in the germ-line.